Relação entre clima organizacional e comprometimento de colaboradores: um estudo de caso no setor turístico - Araújo, José Mateus Silva de (2019)
The Studies in the area of people management have been growing increasingly in the context of current research in the tourism sector, since organizations in this area have been focusing attention on their employees, aiming at consolidating the provision of quality services to the clients of its enterprise, as a method of differentiation in the market. Through this scenario, this article aims to analyze the relationship between organizational climate and commitment in a tourist company of the city of Natal/RN, and also as specific objectives: a) characterize the dimensions of the organizational climate; b) Describe the approaches of organizational commitment; c) Understand the relationships between the organizational climate and the commitment of employees. The research fit as descriptive, quantitative approach, and was developed through the application of questionnaires to the employees of a Christmas tourist enterprise. As a result, it was possible to understand the detailing of climate dimensions, the strong relation of categories and the direct interference in workers' perceptions about the organization. Understand the focus of commitment that has more relevance to the company. Finally, the established correlations between the dimensions of the studied constructions were identified.